Maternal Pre-pregnancy Body Mass Index Categories and Infant Birth Outcomes: A Population-Based Study of 9 Million Mother–Infant Pairs - Zong, Xin'nan; Wang, Huan; Yang, Liu; Guo, Yajun; Zhao, Min; Magnussen, Costan G.; Xi, Bo (Frontiers in Nutrition, 2022)
Background/Aims Infant adverse birth outcomes have been suggested to contribute to neonatal morbidity and mortality and may cause long-term health consequences. Although evidence suggests maternal pre-pregnancy body mass index (BMI) categories associate with some birth outcomes, there is no consensus on these associations. We aimed to examine the associations of maternal pre-pregnancy BMI categories with a wide range of adverse birth outcomes. Methods Data were from a population-based retrospective cohort study of 9,282,486 eligible mother-infant pairs in the U.S. between 2016 and 2018. Maternal pre-pregnancy BMI was classified as: underweight (<18.5 kg/m2); normal weight (18.5-24.9 kg/m2); overweight (25.0-29.9 kg/m2); obesity grade 1 (30-34.9 kg/m2); obesity grade 2 (35.0-39.9 kg/m2); and obesity grade 3 (≥40 kg/m2). Six birth outcomes of the newborn included preterm birth, low birthweight, macrosomia, small for gestational age (SGA), large for gestational age (LGA) and low Apgar score (5-minute score<7). Results Maternal pre-pregnancy overweight and obesity increased the likelihood of infant preterm birth, with odds ratios (ORs) (95% confidence intervals, CIs) of 1.04 (1.04-1.05) for overweight, 1.18 (1.17-1.19) for obesity grade 1, 1.31 (1.29-1.32) for obesity grade 2 and 1.47 (1.45-1.48) for obesity grade 3, as well as for pre-pregnancy underweight (OR=1.32, 95% CI=1.30-1.34) after adjusting for all potential covariates. Pre-pregnancy overweight and obesity were associated with higher odds of macrosomia, with ORs (95% CI) of 1.53 (1.52-1.54) for overweight, 1.92 (1.90-1.93) for obesity grade 1, 2.33 (2.31-2.35) for obesity grade 2, and 2.87 (2.84-2.90) for obesity grade 3. Pre-pregnancy overweight and obesity was associated with higher odds of LGA, with OR (95% CIs) of 1.58 (1.57-1.59) for overweight, 2.05 (2.03-2.06) for obesity grade 1, 2.54 (2.52-2.56) for obesity grade 2, and 3.17 (3.14-3.21) for obesity grade 3. Pre-pregnancy overweight and obesity were also associated with higher odds of low Apgar score, with ORs (95% CIs) of 1.12 (1.11-1.14) for overweight, 1.21 (1.19-1.23) for obesity grade 1, 1.34 (1.31-1.36) for obesity grade 2, and 1.55 (1.51-1.58) for obesity grade 3. Conclusion Our findings suggest maintaining or obtaining a healthy body weight for pre-pregnancy women could substantially reduce the likelihood of important infant adverse birth outcomes.